Urine-based assays for inpatients with HIV-associated tuberculosis in rural South Africa - Mbulelo Mntonintshi; Bianca Sossen; Hloni Bookholane; Aimee Lifson; Lisa Africa; René Goliath; Nicola Wearne; Andy Parrish; Graeme Meintjes (Southern African Journal of HIV Medicine)
Background: Accurate non-sputum-based tuberculosis (TB) diagnostics are urgently needed to improve diagnostic yield and patient outcomes.